Bombyx ortholog of the Drosophila eye color gene brown controls riboflavin transport in Malpighian tubules. (January 2018) - Zhang, Haokun; Kiuchi, Takashi; Hirayama, Chikara; Katsuma, Susumu; Shimada, Toru
Abstract: The Drosophila eye color gene brown is known to control the transport of pteridine precursors in adult eyes. The Brown protein belongs to the ATP-binding cassette (ABC) transporter G family, which includes proteins encoded by the genes brown, scarlet, and white. These genes are responsible for pigmentation in Drosophila and the domestic silkworm Bombyx mori . Although orthologs of brown are conserved among insects, the function of this gene is only known in Drosophila . Here, we elucidated the function of the B . mori ortholog Bm-brown . We examined the spatial and temporal expression profiles of Bm-brown and found that this gene was specifically and continuously expressed in larval Malpighian tubules (MTs), indicating this gene has a special function in MTs. We then successfully obtained a Bm-brown knockout (KO) strain based on a wild-type (WT) strain using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated nuclease 9 (Cas9) system. We found that larval MTs of the KO strain were white, whereas those of WT were yellow. It is known that larval yellow MTs of WT are due to the accumulation of riboflavin. Therefore, we compared the riboflavin contents of MTs of KO and WT strains, and found that the riboflavin level in the KO strain was 20 fold less than that in WT during the 5th instar period. MTs are known to exhibit a similar milky color in w-3 mutant larvae due to a deficiency of riboflavin accumulation. The responsible gene for w-3 mutant is the Bmwh3 gene, which is orthologous to Drosophila white . Thus, we speculate that Bm-brown is heterodimerized with Bmwh3, similar to Brown/White in Drosophila, and acts as a riboflavin transporter in silkworm MTs. Graphical abstract: Highlights: Bombyx mori brown gene ( Bm-brown ) is specifically expressed in the larval Malpighian tubules. We generated a Bm-brown KO mutant using the CRISPR/Cas9 system. Bm-brown encodes an ABC transporter for riboflavin in Malpighian tubule.